Assessments of Selected Essential Elements in Canned Tuna Marketed in Jordan - A. Ababneh, Fuad (Asian Journal of Chemistry, 2012)
In this study, the levels of five macroelements and eight microelements in 104 samples of canned tuna were determined by ICP-OES and flame photometer. The concentrations of macroelements were found in the range of 1947-3963 mg/kg for phosphorous, 1044-2883 mg/kg for potassium, 665-2022 mg/kg for sodium, 241- 457 mg/kg for magnesium and 107-384 mg/kg for calcium. The contents of investigated microelements in canned tuna samples were found to be in the range 4.1-21.1 mg/kg for iron, 3.0-12.1 mg/kg for zinc, 0.12-0.92 mg/kg for copper, 0.11-1.07 mg/kg for selenium, < 0.02 to 0.81 mg/kg for manganese, < 0.04-0.23 mg/kg for chromium, < 0.03-0.07 mg/kg for cobalt and < 0.04-0.06 mg/kg for molybdenum. The results were compared with the literature values.